EXPLORING JAPANESE POLITENESS STRATEGIES IN MORIARTY THE PATRIOT: A PRAGMATIC ANALYSIS OF WILLIAM JAMES MORIARTY’S UTTERANCES - Defi Rahmawati; Dwi Puji Asrini (Universitas Islam Sumatera Utara (UISU), 2026)
This study investigates the politeness strategies employed by William James Moriarty in the anime Moriarty the Patriot from a pragmatic perspective to identify the types of politeness strategies used by the character and examine their communicative functions within social interactions. Using a descriptive qualitative approach, the data were collected from episodes 1–11 through observation, listening, and transcription techniques. The data were then analyzed using Brown and Levinson’s (1987) politeness theory, which classifies politeness strategies into bald on-record, positive politeness, negative politeness, and off-record strategies. The findings reveal that all four strategies appear in William’s utterances, with negative politeness and positive politeness occurring most frequently. These strategies are used not only to maintain social harmony and demonstrate respect, but also to construct authority, manipulate psychological responses, and control communication in various situations. Furthermore, the study shows that Japanese politeness is highly contextual and closely connected to indirectness, social hierarchy, interpersonal relationships, and communicative intentions. This research contributes to pragmatic studies on Japanese politeness in anime, particularly within the crime-thriller genre, by highlighting the dynamic relationship between politeness, power, and psychological communication in fictional discourse.